Application For Growth And Human Development Advanced Level Student Learning Schools First Using Macromedia Flash 8.0. - Tri Agus Tina Atha; Dewi Melani Lusita, SKom., MMSI (Jurnal Sistem Informasi, 2008)
Application Program Growth And Human Development Learning School ForAdvanced Level One is a multimedia application that contains some material abouthuman development for children or junior secondary students in accordance withexisting guidelines on the books today that are packed in an attractive form and canbe used as learning materials and can facilitate students to learn more about humangrowth and development.Keywords: Human